The Safe Environment for Every Kid Model in the Swedish Child Health Services: Adoption and Introduction in a Healthcare Region - Marie Golsäter; Ann‐Christine Andersson (Wiley, 2024)
ABSTRACT Background Early support for children and families in need can improve children's health and development. In a Swedish region, a new working model called Safe Environment for Every Kid (SEEK) was introduced in the Child Health Services to facilitate the early identification of psychosocial risk factors. Objective The aim of this study was to describe the adoption and introduction of the SEEK model in the Child Health Services of Region Jönköping County. Methods Quantitative data were analysed using descriptive statistics, whereas qualitative data were analysed separately by a thematic approach. The results were then interpreted together with documents (including CHS management meeting notes and documents describing planning and training sessions) using an exploratory mixed‐methods approach to give a comprehensive description of the adoption and introduction of the SEEK model. Results The results show that the SEEK model improved coordination and collaboration, which led to better integrated care for children and families. The structure was regarded as supportive when introducing the SEEK model in Child Health Services. The questionnaire, as part of the SEEK model, was used in 88% of possible health visits. The most reported reason for not using it was a lack of time. Conclusions The desire to make a difference and thereby promote better health and development for children was a crucial factor for the nurses in adopting the SEEK model in their clinical practice. The design using coaches was also appreciated and supported the adoption and introduction of the SEEK model. Patient or Public Contribution Parents and healthcare professionals did not contribute to the research process. The results are based on dialogues between CHS nurses and parents after the parents filled in the SEEK questionnaire, providing an understanding of professional relationships when dealing with challenging issues.